The Influence of Initial Possession Level on Consumers' Adoption of a Collection Goal: A Tipping Point Effect. (November 2014) - Gao, Leilei; Huang, Yanliu; Simonson, Itamar
Previous research has typically treated collection as a top-down process and focused on its later stages. However, collections may start by accident and are often triggered by incidental, bottom-up factors. The authors propose that a small number of possessions (i.e., a few more than one) represent an unjustified and, thus, unstable possession level that prompts a status change. They examine the collection tipping point at which obtaining items belonging to a series (e.g., a couple of collectible Coke cans) often gives rise to a decision to start a collection. Consumers then seek additional items to fulfill their emerging goal. In six lab studies and one field study, the authors investigate the tipping point at which a collection "project" begins and explore the psychological processes underlying that tipping point. In addition, they discuss the theoretical and managerial implications of this research.